If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(x + -4) = x + -4 Reorder the terms: 3x(-4 + x) = x + -4 (-4 * 3x + x * 3x) = x + -4 (-12x + 3x2) = x + -4 Reorder the terms: -12x + 3x2 = -4 + x Solving -12x + 3x2 = -4 + x Solving for variable 'x'. Reorder the terms: 4 + -12x + -1x + 3x2 = -4 + x + 4 + -1x Combine like terms: -12x + -1x = -13x 4 + -13x + 3x2 = -4 + x + 4 + -1x Reorder the terms: 4 + -13x + 3x2 = -4 + 4 + x + -1x Combine like terms: -4 + 4 = 0 4 + -13x + 3x2 = 0 + x + -1x 4 + -13x + 3x2 = x + -1x Combine like terms: x + -1x = 0 4 + -13x + 3x2 = 0 Factor a trinomial. (1 + -3x)(4 + -1x) = 0Subproblem 1
Set the factor '(1 + -3x)' equal to zero and attempt to solve: Simplifying 1 + -3x = 0 Solving 1 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -3x = 0 + -1 -3x = 0 + -1 Combine like terms: 0 + -1 = -1 -3x = -1 Divide each side by '-3'. x = 0.3333333333 Simplifying x = 0.3333333333Subproblem 2
Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4Solution
x = {0.3333333333, 4}
| x-2=-15x^2 | | 18+11q=84 | | 32z=64 | | -32+6x=-8(4-8x) | | 132+2x=180 | | 18x^3y^2/30x^4y^5 | | 6r-17=-25+4r | | 0=-5q-2q | | 5(8x+2y-6)= | | 7z-11=-3+9z | | -8x-8x=64 | | -3q+r+2-q-6r= | | 8.2=2.8(3x-2) | | a^2+9ab-10b^2=0 | | 4x-18=-7(8-6x) | | [x+5]=42 | | 0=x^2+11x-34 | | x^2+0.8x-4.16=0 | | -x=(-2/9) | | n-10=5/6-7-1/3n | | 45+2x=180 | | 5q+2y-1+3q-5y= | | 3d+2(5d+4)=47 | | -2(8+3a)=24-a | | y^8-32y^4+256=0 | | u^2+3uv=0 | | -3x^2+525x-19602=0 | | log(8)(-3s+12)=log(8)(-7s+4) | | 6(4+4a)=24-4a | | m^2-11mn+10n^2=0 | | p^2+4p-43=0 | | 3n^3+21n^2-5n-35=0 |